Knowledge and Attitude’s Men in Family Planning with Stop Motion Video Design in Tasikmalaya District - Hapi Apriasih; Tupriliany Danefi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Indonesia is facing problems with the quantity and quality of human resources. One of the controls on this population is the family planning program. Currently, implementation of development-oriented to justice and gender equality in Indonesia has been implemented, it needs efforts to increase men's participation in family planning, namely by promoting media using digital marketing, one of which is by stop motion animation video media. The purpose of this study is to know the differences in knowledge and attitudes of men/husbands about male contraception in family planning before and after the screening of stop motion videos and to know the picture of male participation in family planning. The research method used was Pre-Experimental with one group pre-test and post-test design. The statistical test used is Wilcoxon. Based on data in Tasikmalaya in 2017 the coverage of contraceptive use from 8589 active acceptors there were 134 condom users (1.56%) and 10 MOP (0.11%) while in 2018 the contraceptive use coverage of 9376 active acceptors contained users 134 condoms (0.014%) and MOP 14 people (0.10%) the data shows that although there was an increase in the number of active family planning acceptors which was 0.22%, the number of male acceptor users decreased including 0.01% MOP and condom 1,54%. An increase in average knowledge after video viewing to 72.42 with an increase of 16.08 for knowledge and attitude variables to become 33.77 with an increase of 1.65 it illustrates the use of video stop motion media effective in increasing male knowledge.